PENGARUH TEPUNG TEMPE DAN VIRGIN COCONUT OIL (VCO) TERHADAP MUTU NUTRISI DAN SENSORIS KERIPIK JAGUNG-TEMPE: The Effect of Ratio of Tempe Flour and Virgin Coconut Oil (VCO) on Nutritional Quality and Sensory of Corn- Tempe Chips - dimas adi putra; M. Abbas Zaini; Dody Handito (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2018)
ABSTRACT The purpose of this study was to determine the effect tempe flour and virgin coconut oil (VCO) on nutritional quality (fat, protein), development volume, crispness, color and sensory corn-tempe chips. The experimental design of this study used a Completely Randomized Design (CRD) with a single factor experiment (tempe flour and VCO) consisting of 6 treatments i.e. PI (40% Tempe Flour: 0% VCO), P2 (Tempe Flour 39% : 1% VCO), P3 (38% Tempe Flour: 2% VCO), P4 (37% Tempe Flour: 3% VCO), P5 (36% Tempe Flour, 4% VCO), P6 (35% Tempe Flour: VCO 5%) with three times replications. The data were analyzed by analysis of variance at the level of 5% if there were significant differences then tested further using Orthogonal Polynominal and tested further with the HSD. Chemical test results showed that the tempeh flour and virgin coconut oil (VCO) has a significant effect on fat content, protein, development volume, crispness, color, texture (hedonic) and color (scoring), but no-significant effect on hedonic (color, taste and texture) and scoring (aroma, taste and texture). The results showed that the tempe and virgin coconut oil (VCO) to P6 was 35%: 5%, the best results were seen from the fat content of 8.65, protein content 15.75, development volume 1.92; crispness rate 13.58; yellow red color (L-46.63,